Effect of Couple-Stress on Peristaltic Transport of Sutterby Fluid in an Asymmetric Channel - Mohammed, Asmaa; Hummady, Liqaa Zeki (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this paper, the effect of a couple–stress and other variables on the peristaltic flow of Sutterby fluid in an inclined asymmetric channel containing a porous medium with heat transfer is examined. In the presence of rotation and couple–stress, mathematical modeling is developed using constitutive equations based on the model of Sutterby fluid. In flow analysis, assumptions such as long wavelength approximation and low Reynolds number are used. The resulting nonlinear equation was numerically solved using the perturbation method. The effects of various physical parameters such as the couple-stress parameter, the Grashof number, the Hartmann number, the Reynold number, the Froude number, the Hall parameter, the Darcy number, the magnetic field, the Sutterby fluid parameter, and heat transfer analysis on the stream function are analyzed graphically. Utilizing MATHEMATICA software, numerical results were computed.